Interspeech 2007 2007
DOI: 10.21437/interspeech.2007-52
|View full text |Cite
|
Sign up to set email alerts
|

Topic in dialogue: prosodic and syntactic features

Abstract: We investigate the relationship between phonetic phrasing, tonal pattern and phrase structure in left peripherical sentence topic. Our corpus consists of three task-oriented Italian dialogues. The results of prosodic analysis show that topics are usually associated to the highest pitch values in the Tone Unit, regardless to their actual syntactic position. Syntactic analysis shows that, while topic phrase structure is rather variable, topic function is quite stable, i.e., topics have mostly circumstantial-loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…Starting from the syntactic features, in most cases the topic is constituted by Noun Phrases performing the function of subject and with light weight, in line with previous studies (Crocco & Savy, 2007;Voghera & Turco, 2008), even if both phrase structure and weight are quite variable (Table 3). Among the syntactic features considered, Weight appears to have the most effect on the phonetic realization of topical expressions.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Starting from the syntactic features, in most cases the topic is constituted by Noun Phrases performing the function of subject and with light weight, in line with previous studies (Crocco & Savy, 2007;Voghera & Turco, 2008), even if both phrase structure and weight are quite variable (Table 3). Among the syntactic features considered, Weight appears to have the most effect on the phonetic realization of topical expressions.…”
Section: Discussionsupporting
confidence: 85%
“…As for syntactic Weight, Voghera & Turco (2008) provide a scale for verbal phrases and for nominal phrases (Noun, Predicative Noun and Prepositional Phrases). We refer to the nominal scale since Crocco & Savy (2007) found that topics are mostly realized as Noun, Prepositional and Adverbial Phrases. The scale takes into account both phrases' structure and expansion and considers five levels of weight according to the presence/absence of determiners (det) and modifiers (mod) and whether the head is a noun or a pronoun (pro):…”
Section: Syntactic Featuresmentioning
confidence: 99%
See 3 more Smart Citations